It's better this way : a novel - Macomber, Debbie (New York : Ballantine Books, 2021)
After divorce shatters her family, one woman's struggle to pick up the pieces finally leads to a new beginning--but is the past truly behind her?
"A novel."
Keywords: Divorce -- Fiction; Families -- Fiction; Interior decorators -- Fiction; Consultants -- Fiction; Divorced people -- Fiction; Condominiums -- Fiction; Adult children of divorced parents -- Family relationships -- Fiction; Man-woman relationships -- Fiction; Seattle (Wash.) -- Fiction; Domestic fiction; Romance fiction